I can be the change I want to be self-efficacy, self-stigma and willingness of juvenile delinquents to desist from criminal behaviors. - Elin, Ann Geline Puod
This quantitative study tried to understand the process of desistance from criminal behaviours by examining thirty-nine Children in Conflict with the Law (CICL) in Western Visayas. Correlation and moderation analyses were employed to understand the dynamics of the variables in focus: self-efficacy, self-stigma, and willingness to desist from criminal behaviours. Survey method was used to collect data from the participants. Data were analyzed using Pearson Product-Moment Correlation and Linear Regression. Results show that self-efficacy was positively correlated with the willingness to desist from criminal behaviours. On the other hand, self-stigma did not prove to have a significant correlation with self-efficacy and the willingness to desist from criminal behaviors respectively. In addition, self-stigma did not moderate the relationship between self-efficacy and the willingness to desist from criminal behaviours. This paper calls for an evaluation of the current juvenile justice system in the Philippines and opens an extension for research in desistance with implications on methodological and theoretical improvement.